2022
DOI: 10.1063/5.0075246
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizations and field-driven core reversals of magnetic vortices in Fe3Sn2 disks

Abstract: A magnetic vortex is a structure with a polarized core surrounded by an in-plane spin swirl and was first reported in easy-plane disks. Here, we explore the effects of the disk thickness, temperature, and out-of-plane field on the magnetic vortex stabilization and core reversals in Kagome uniaxial ferromagnetic Fe3Sn2 disks. Magnetic ground domains in Fe3Sn2 disks turn from stripes to vortices after decreasing the disk thickness or temperature as the easy-plane anisotropy wins the competition with the uniaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A previous study has shown that the magnetic ground state in ferromagnetic nanodisks with 𝜂 < 1 can be manipulated by thickness. [37] In our case of 𝜂 = 0.22, the skyrmion bubble cannot be stabilized when the thickness of the nanostripe is smaller than 65 nm for 𝜂 = 0.22. The small 𝜂 suggests that dipole-dipole interaction plays a vital role in stabilizing the skyrmion bubble.…”
Section: Resultsmentioning
confidence: 55%
“…A previous study has shown that the magnetic ground state in ferromagnetic nanodisks with 𝜂 < 1 can be manipulated by thickness. [37] In our case of 𝜂 = 0.22, the skyrmion bubble cannot be stabilized when the thickness of the nanostripe is smaller than 65 nm for 𝜂 = 0.22. The small 𝜂 suggests that dipole-dipole interaction plays a vital role in stabilizing the skyrmion bubble.…”
Section: Resultsmentioning
confidence: 55%
“…The induced magnetic field amplitudes capable of chirality reversal for the 20 nm thick disc are not very different from that reported in ref. 47 both via experiments and via micromagnetic simulations, pointing out to the local nature of the reversal process as the dimensions of the discs studied therein are considerably greater. The foregoing discussion focuses on the disc thickness for a fixed disc diameter.…”
Section: Resultsmentioning
confidence: 96%